Pedagogics and the School of Michael Schetinin - Lumír Ries (Czech Pedagogical Society, 2010)
The unique boarding school of Michael Schetinin in Russia is an organiccomplex of primary and secondary education with an expressively spiritual conceptionof education. Essential features of education include: national cultural orientation,holistic concept of the man and the world; moral-spiritual self-development; absorptionin cognition; practical labor activities; daily artistic activities; physical efficiency.Meeting, human relations, intercommunity help to determine teaching style ineducational work groups of diverse age (there are no classes). Concentrated learning isfocused on one field (subject) until the secondary school level is obtained (there are nolessons). Pupils play teacher's roles along with their educators. Most pupils attend orgraduate a co-operating university at the same time.